The Effect Of Proactive Personality and Organizational Support For Career Development On Career Satisfaction - Fadlilah Karunia Novianti; Gandi Aswaja Yogatama (Universitas Muhammadiyah Prof. DR HAMKA., 2019)
Employee Career satisfaction is an important element that needs to be managed by the organization. This study aims to find evidence of the important role of mediating Career Management Behavior in the role of Organizational Support for Career Development and Proactive Personalities towards Career satisfaction. This type of research is quantitative research. The population used in this study were all employees of PT Barito Putera who got 44 people. This study uses census techniques in sampling. While the analysis technique is used is partial least square (PLS) with the help of SmartPLS3 software. The results of this study indicate that Career Management Behavior can mediate the effect of Proactive personality and Organizational Support for Career Development on Career satisfaction.